AKIBAT HUKUM TIDAK TERPENUHINYA JANJI UNTUK MELANGSUNGKAN PERKAWINAN : Kajian Putusan Pengadilan Negeri Maumere No.: 8/Pdt.G/2019/PN Mme - Yori, Aurelius Kasimirus; Johan, Yehezkiel Reynaldi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The Verdict of Maumere Public Court Number 8/Pdt.G/2019/PN.Mme, in case of compensation claiming for the denying of the defendant to marry with the claimant that qualified as wanprestatie (disclaiming) is basically incorrect. The oral understanding kept on rolling the claimant and the defendant before is legally speaking unfulfilled the elements of Chapter 1320 BW. It is implied by the uncontextual frame. In one side, the object of the understanding between claimant and defendant requlated within Title I BW. On another side, the context above is basically not the legal frame of Creditor-Debtor within Title III BW. In this case, judge should decide that the claiming was unacceptable (Niet Onvankelijke Verklaard). The claimant is able to reconstruct the claiming and propose a new one so that the new claiming could not be classified as Ne Bis In Idem